Single-cell RNA sequencing unveils the communications between malignant T and myeloid cells contributing to tumor growth and immunosuppression in cutaneous T-cell lymphoma. (28th December 2022) - Du, Yuxin; Cai, Yun; Lv, Yan; Zhang, Lishen; Yang, Hao; Liu, Quanzhong; Hong, Ming; Teng, Yue; Tang, Weiyan; Ma, Rong; Wu, Jianqiu; Wu, Jianzhong; et al.
Abstract: Cutaneous T cell lymphoma (CTCL) is characterized by the accumulation of malignant T cells in the skin. However, advanced CTCL pathophysiology remains elusive and therapeutic options are limited due to the high intratumoral heterogeneity and complicated tumor microenvironment (TME). By comparing the single-cell RNA-seq (scRNA-seq) data from advanced CTCL patients and healthy controls (HCs), we showed that CTCL had a higher enrichment of T/NK and myeloid cells. Subpopulations of T cells (CXCR3 +, GNLY +, CREM +, and MKI67 + T cells), with high proliferation, stemness, and copy number variation (CNV) levels, contribute to the malignancy of CTCL. Besides, CCL13 + monocytes/macrophages and LAMP3 + cDC cells were enriched and mediated the immunosuppression via inhibitory interactions with malignant T cells, such as CD47-SIRPA, MIF-CD74, and CCR1-CCL18. Notably, elevated expressions of S100A9 and its receptor TLR4, as well as the activation of downstream toll-like receptor and NF-κB pathway were observed in both malignant cells and myeloid cells in CTCL. Cell co-culture experiments further confirmed that the interaction between malignant CTCL cells and macrophages contributed to tumor growth via S100A9 upregulation and NF-kb activation. Our results showed that blocking the S100A9-TLR4 interaction using tasquinimod could inactivate the NF-κB pathway and inhibit the growth of CTCL tumor cells, and trigger cell apoptosis. Collectively, our study revealed a landscape of immunosuppressive TME mediated by interactions between malignant T cells and myeloid cells, and provided novel targets and potential treatment strategies for advanced CTCL patients. Highlights: CTCL has a higher enrichment of T and myeloid cells compared with healthy controls (HCs). T cell subpopulations with high proliferation, stemness and CNV levels, contribute to the malignancy of CTCL. CCL13+ mono/macrophages and LAMP3+ cDC cells interact with malignant T cells to shape the immunosuppression of CTCL. NF-κB pathway induced by S100A9 and TLR4 interaction is activated in both malignant and myeloid cells in CTCL. Blocking the S100A9-TLR4 interaction could inactivate the NF-κB pathway and inhibit the growth of CTCL tumor cells.